Creation of a Mini Library to Improve Children's Literacy Skills at SB At-Tanzil Kg Lindungan Malaysia - Nurlaili Dina Hafni; Chabibah Alamsyah; Afifatul Askha (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study aims to improve the literacy skills of Indonesian migrant workers' children at SB At-Tanzil Kg Lindungan, Malaysia, through the creation and utilization of a mini library as a contextual learning medium. This study uses a classroom action research (CAR) method implemented in two cycles, with stages of planning, action implementation, observation, and reflection. The research subjects were 20 elementary school students at SB At-Tanzil. Data collection techniques included observation, interviews, literacy skills tests, and documentation. Data analysis was conducted descriptively and qualitatively by comparing the results between cycles. The research results showed a significant improvement in children's literacy skills after the implementation of the mini library. In cycle I, most students were just beginning to get used to reading and writing simple summaries. However, in cycle II, students showed improvements in reading comprehension, better structured writing, and increased interest in and habit of reading daily. The mini library successfully created a conducive, enjoyable, and accessible literacy environment for migrant children. This improvement in literacy skills aligns with constructivist theory (Piaget, 1972; Vygotsky, 1978), which emphasizes the importance of interaction with the learning environment, and emergent literacy theory (Clay, 1991), which explains that literacy develops through meaningful reading experiences. The research results also support the concept of Contextual Teaching and Learning (Johnson, 2007), where learning linked to children's real lives fosters learning motivation and active engagement. Overall, this study concludes that creating a mini library is an effective strategy for improving the literacy skills of migrant workers' children. This program can be used as a model for inclusive and sustainable community-based literacy learning in educational environments for Indonesian children abroad.